2023
DOI: 10.3390/nu15041053
|View full text |Cite
|
Sign up to set email alerts
|

The Complexities of Managing Gestational Diabetes in Women of Culturally and Linguistically Diverse Backgrounds: A Qualitative Study of Women’s Experiences

Abstract: Aim: This study aimed to explore women’s perspectives and experiences concerning how culture impacts the lifestyle management of gestational diabetes mellitus (GDM) in women of culturally and linguistically diverse (CALD) backgrounds. Methods: Women of any cultural background diagnosed with GDM within the previous 12 months were purposively recruited from two Australian metropolitan hospitals. Data collected using semi-structured interviews (n = 18) and focus groups (n = 15 women in three groups) were analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…One of the main challenges for managing GDM was a lack of culturally specific advice for dietary adjustments, in keeping with evidence from previous studies ( 18 , 23 , 24 ). Surprisingly, even Australian-born women adhering to specific diets, such as vegetarian, found that the dietary advice for managing GDM was inadequate.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…One of the main challenges for managing GDM was a lack of culturally specific advice for dietary adjustments, in keeping with evidence from previous studies ( 18 , 23 , 24 ). Surprisingly, even Australian-born women adhering to specific diets, such as vegetarian, found that the dietary advice for managing GDM was inadequate.…”
Section: Discussionsupporting
confidence: 73%
“…Surprisingly, even Australian-born women adhering to specific diets, such as vegetarian, found that the dietary advice for managing GDM was inadequate. Restricting the consumption of cultural foods and the fear of eating were also reported in other studies (18,(23)(24)(25). Better education about food cultures and diets among health professionals can provide more tailored dietary information to women of all ethnicities.…”
Section: Management Issuessupporting
confidence: 57%
“… 63 This approach could also benefit other priority groups where stigma around life-style changes can be common (e.g culturally and linguistically diverse populations (CALD) and women who are pregnant). 64 , 65 , 66 Pharmacist referral criteria were based on HbA1c result together with or without prior diagnosis of diabetes. On reflection, a high BGL result (more than 10 mmol/L for more than 24 h) could also trigger a referral for endocrine review, as it currently does for medical teams.…”
Section: Discussionmentioning
confidence: 99%